Dampak Putusan Mahkamah Konstitusi Tahun 2016 Terhadap Eksistensi Penghayat Kepercayaan Sapta Darma di Ponorogo - Nugroho, Rofi Aji (Journal of Comparative Study of Religions, 2025)
Belief or spirituality in Indonesia used to be a practice embraced by some people. Today, it has evolved into a form of belief in God Almighty, which leads to the understanding that its adherents do not belong to a particular religious category. Post-reform, these believers, including those who adhere to Sapto Darmo, experience social pressure from society, which causes them to feel restricted in carrying out their worship. Nonetheless, Sapto Darmo believers have managed to overcome these obstacles, even though they are forced to follow the prevailing religious lessons in schools. This study aims to determine the condition of Sapto Darmo believers in Ponorogo after the decision of the Constitutional Court and to know the government's protection of the civil rights of spirituality. The researcher uses the Grounded Research method and the sociology of religion approach which aims to find out the condition of Sapto Darmo believers in Ponorogo after the Constitutional Court's decision and to find out the government in protecting the civil rights of believers. In understanding the Sapto Darmo believers and knowing how the existence of Sapto Darmo in Ponorogo, the results of this study can be taken are, The government's attitude to citizens and this circular letter to follow up on the Constitutional Court Decision Number 97 / PUU-XIV / 2016 dated October 18, 2017 and the Minister of Home Affairs Regulation Number 118 of 2017 concerning Family Card Blanks, Registers and Civil Registration Certificate Excerpts.